2017
DOI: 10.1038/s41467-017-00942-5
|View full text |Cite
|
Sign up to set email alerts
|

Survival of pancreatic cancer cells lacking KRAS function

Abstract: Activating mutations in the proto-oncogene KRAS are a hallmark of pancreatic ductal adenocarcinoma (PDAC), an aggressive malignancy with few effective therapeutic options. Despite efforts to develop KRAS-targeted drugs, the absolute dependence of PDAC cells on KRAS remains incompletely understood. Here we model complete KRAS inhibition using CRISPR/Cas-mediated genome editing and demonstrate that KRAS is dispensable in a subset of human and mouse PDAC cells. Remarkably, nearly all KRAS deficient cells exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
169
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(176 citation statements)
references
References 71 publications
7
169
0
Order By: Relevance
“…To elucidate potential non-mutational mechanisms of PDAC progression, we performed bulk RNA-sequencing (RNA-seq) on pancreata from obese KCO and non-obese KC and KPC mice exhibiting comparable tumor burden (Table S6), permitting analyses of both tumor cells and their microenvironment in cancer pathogenesis. Using Independent Component Analysis (ICA), an unsupervised blind source separation technique (Hyvarinen and Oja, 2000;Muzumdar et al, 2017), we identified gene expression signatures associated with inflammation and fibrosis as upregulated in KCO compared to KC/KPC mice (Figures 4A-D and Tables S7-S8), likely representing obesity-associated alterations in the tumor microenvironment. We confirmed abundant extracellular matrix deposition and immune cell infiltration by histologic analyses of KCO tumor sections ( Figure 4E).…”
Section: Enhanced Tumor-associated Inflammation and Fibrosis In Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…To elucidate potential non-mutational mechanisms of PDAC progression, we performed bulk RNA-sequencing (RNA-seq) on pancreata from obese KCO and non-obese KC and KPC mice exhibiting comparable tumor burden (Table S6), permitting analyses of both tumor cells and their microenvironment in cancer pathogenesis. Using Independent Component Analysis (ICA), an unsupervised blind source separation technique (Hyvarinen and Oja, 2000;Muzumdar et al, 2017), we identified gene expression signatures associated with inflammation and fibrosis as upregulated in KCO compared to KC/KPC mice (Figures 4A-D and Tables S7-S8), likely representing obesity-associated alterations in the tumor microenvironment. We confirmed abundant extracellular matrix deposition and immune cell infiltration by histologic analyses of KCO tumor sections ( Figure 4E).…”
Section: Enhanced Tumor-associated Inflammation and Fibrosis In Obesitymentioning
confidence: 99%
“…All reads that passed quality metrics were mapped to UCSC mm9 mouse genome build (http://genome.ucsc.edu/) using RSEM (v1.2.12) (http://deweylab.github.io/RSEM/). All RNAseq analyses were conducted in R. High-resolution signature analyses between tumors from obese (KCO and KCO treated with AAV-GFP) and non-obese (KC and KPC) models were performed using a blind source separation methodology based on Independent Component Analysis (ICA), as previously described (Hyvarinen and Oja, 2000;Muzumdar et al, 2017).…”
Section: Mouse Tumor Rna Sequencing (Rna-seq) and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, developing direct inhibitors of oncogenic KRAS signaling has been found to be extremely challenging and, as of to date, no suitable inhibitors are available for routine application outside of early clinical and preclinical studies [30,31,32,33,34,35,36]. Moreover, accumulating preclinical evidence already suggests that, although being a potentially powerful therapeutic approach, pharmacological inhibition of oncogenic KRAS signaling alone will likely not be sufficient to fully eradicate and cure metastatic pancreatic cancer [27,29]. …”
Section: Novel Therapeutic Targetsmentioning
confidence: 99%
“…At the same time PDAC cells appear to maintain dependence on oncogenic Ras signaling for survival and proliferation [26,27,28]. Therefore, pharmacologically inhibiting oncogenic KRAS signaling has been suggested for a long time and is still considered as the Holy Grail in the quest for targeted therapeutic approaches directed against pancreatic cancer by many authors [29]. Nevertheless, developing direct inhibitors of oncogenic KRAS signaling has been found to be extremely challenging and, as of to date, no suitable inhibitors are available for routine application outside of early clinical and preclinical studies [30,31,32,33,34,35,36].…”
Section: Novel Therapeutic Targetsmentioning
confidence: 99%